Acrylate–gelatin–carbonated hydroxyapatite (cHAP) composites for dental bone-tissue applications. Issue 6 (3rd September 2020) - Golubevas, Ricardas; Stankeviciute, Zivile; Zarkov, Aleksej; Golubevas, Raimundas; Hansson, Lars; Raudonis, Rimantas; Kareiva, Aivaras; Garskaite, Edita
Abstract : The favourable properties of acrylate–gelatin–cHAP composites fabricated via copolymerization reaction may make possible porosity and hydrophilicity remodelling and thus promote scaffold-implant integration. Abstract : Various types of scaffolds made of synthetic polymers have been widely studied for bone-tissue applications due to their mechanical strength, biocompatibility and biodegradability, but the hydrophobic nature of synthetic polymers and frequent absence of pores within the scaffolds inhibit cellular attachment, infiltration, and tissue ingrowth. In this study, multi-composite scaffolds composed of dipentaerythritol hexa-acrylate (DPHA), ethylene glycol dimethacrylate (EGDMA), gelatin, and carbonated hydroxyapatite (cHAP) have been made. Percentage ratio of polymer matrix to gelatin was varied 50/50, 75/25, and 95/5 to change the porosity of the resultant scaffolds. The structure, crystallinity, and phase composition of the cHAP were confirmed by FTIR, Raman, XRD and Rietveld analyses, TG/DSC was used to evaluate the distribution of ceramics within the polymer matrix, and FTIR-ATR was used to confirm the molecular structure of composites. SEM/EDS analysis of the scaffolds revealed cavities and irregularities in the surface, and that cHAP was indistinctly exposed on the composite surface, computed tomography (CT) was used to estimate the density and homogeneity of the scaffolds, and the cHAP distribution within the scaffolds was evaluated by conventional radiography. The hydrophilicity of the multi-composite scaffolds was investigated using an aqueous solution of methylene blue dye which showed that the acrylate(75%)–gelatin(25%)–cHAP composite had the highest hydrophilicity. The results suggest that acrylate–gelatin–cHAP scaffolds have a potential for bone-tissue engineering.